2015
DOI: 10.15828/2075-8545-2015-7-4-121-142
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultra cellulose fiber for the enhancement of the durability and shrinkage of cement pastes exposed to normal and aggressive curing conditions

Abstract: Ultra Cellulose Fibers are hydrophilic fibers which can hold most of their weight water when it is mixed into concrete, after concrete is hardened, these fibers will slowly release this water to unhydrated cement during the critical early phases of curing which assist in more complete hydration, this internal self curing action results in more completely hydrated cement which contributes to more strength development and more control of internal microcracking, particularly when normal curing is not adequate. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…6 show that the ratio between σ t and σ c tends to the expected results. Generally there is a decrease in σ t /σ c as cement content increased at 28 days as reported by many investigators [15] and [16] since they stated that as the compressive strength of concrete increased, the tensile strength decreased and consequently there is a decrease in σ t /σ c Also, there is a similar effect of cement content on σ t /σ c ratio at 28days and at 56 days for cement mix , and cement+nano as σ t /σ c decreases from 500kg/m 3 to 600kg/m 3 then increased up to 700kg/m 3 but this increase still less than that of 500kg/m 3 by comparing fig (5) and fig (6). For the other three mixes, cement, cement+nano, there is steady behavior of σ t /σ c at 28 days and at 56 days for cement content range from 500 kg/m 3 to 600 kg/m 3 but from 600 kg/m 3 to 700 kg/m 3 the behavior is completely different from 28 days behavior to that 56days for the same three mixes.…”
Section: Table 6: Splitting Tensile Strength Results For the Concrete...mentioning
confidence: 80%
See 2 more Smart Citations
“…6 show that the ratio between σ t and σ c tends to the expected results. Generally there is a decrease in σ t /σ c as cement content increased at 28 days as reported by many investigators [15] and [16] since they stated that as the compressive strength of concrete increased, the tensile strength decreased and consequently there is a decrease in σ t /σ c Also, there is a similar effect of cement content on σ t /σ c ratio at 28days and at 56 days for cement mix , and cement+nano as σ t /σ c decreases from 500kg/m 3 to 600kg/m 3 then increased up to 700kg/m 3 but this increase still less than that of 500kg/m 3 by comparing fig (5) and fig (6). For the other three mixes, cement, cement+nano, there is steady behavior of σ t /σ c at 28 days and at 56 days for cement content range from 500 kg/m 3 to 600 kg/m 3 but from 600 kg/m 3 to 700 kg/m 3 the behavior is completely different from 28 days behavior to that 56days for the same three mixes.…”
Section: Table 6: Splitting Tensile Strength Results For the Concrete...mentioning
confidence: 80%
“…S.I. Zaki (2015) carried out an investigation about assessment of the durability of NS / fly ash cement pastes exposed to normal and aggressive curing conditions he studied the effect of adding fly ash (FA) and NS on the durability of cement pastes under normal and aggressive curing condition .NS was added with different percentages, while FA value was constant (10%). SEM was used to monitor the hydration process and durability.…”
Section: Icasge'19mentioning
confidence: 99%
See 1 more Smart Citation
“…Their research revealed a decrease of approximately 76% in the 28-day drying shrinkage of the mortar when the wastepaper was added at a ratio of 1/16 of the weight of sand. In another study regarding the utilization of cellulose fiber in cement paste, it was found that introducing 0.5% highly refined cellulose fiber (known as ultra cellulose fiber with a chemical formula (C 6 H 12 O 5 ) n ) by the weight of cement resulted in a decrease of approximately 35% in the 28 days drying shrinkage [ 79 ]. Zhang et al [ 80 ] analyzed how the addition of coir as a cellulosic fiber affected the drying shrinkage of cement paste and indicated that incorporating 4% fiber by the weight of cement decreased the 28-day drying shrinkage by approximately 50%.…”
Section: Resultsmentioning
confidence: 99%
“…However, more deterioration was caused by sulfuric acid. It is due to the fact that in the case of sulfuric acid, a product called calcium sulfoaluminate (Ettringite) is formed, which expands and hence causes disruption of the set cement paste [17,20] . The workability decreased with the introduction of bentonite as cement replacement.…”
Section: Weight Lossmentioning
confidence: 99%